Analisis Dampak Pelatihan dan Pengembangan, Kepuasan Kerja, dan Komitmen Organisasional terhadap Kinerja Karyawan - Ni Kadek Suryani; Delyana Rahmawany Pulungan; Itot Bian Raharjo; Yamolala Zega; Muhammad Syafri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of training and development, job satisfaction, and organizational commitment on employee performance. Data collection techniques using observation, interviews and questionnaires to 52 respondents with census techniques. The research method uses causal research. The results of this study are training and development have a positive and significant effect on employee performance. Job satisfaction has a positive effect on employee performance. Organizational commitment has a positive and significant effect on employee performance.